Folding Model Study of the Elastic Alpha-alpha Scattering at Low Energies - Tan, Ngo Ha; Phuc, Nguyen Hoang; Khoa, Dao Tien (Communications in Physics, 2014)
The folding model analysis of the elastic \(α + α\) scattering at the incident energies below the reaction threshold of 34.7 MeV (in the lab system) has been done using the well-tested density dependent versions of the M3Y interaction and realistic choices for the \(^4\)He density. Because the absorption is negligible at the energies below the reaction threshold, we were able to probe the \(α + α\) optical potential at low energies quite unambiguously and found that the α + α overlap density used to construct the density dependence of the M3Y interaction is strongly distorted by the Pauli blocking. This result gives possible explanation of a long-standing inconsistency of the double-folding model in its study of the elastic \(α + α\) and \(α\)-nucleus scattering at low energies using the same realistic density dependent M3Y interaction